Acute electrophysiologic consequences of pyridostigmine inhibition of cholinesterase in humans - Zimerman,L.I. (2010)
The cardiovascular electrophysiologic basis for the action of pyridostigmine, an acetylcholinesterase inhibitor, has not been investigated. The objective of the present study was to determine the cardiac electrophysiologic effects of a single dose of pyridostigmine bromide in an open-label, quasi-experimental protocol. Fifteen patients who had been indicated for diagnostic cardiac electrophysiologic study underwent two studies just before and 90-120 min after the oral administration of pyridostigmine (45 mg). Pyridostigmine was well tolerated by all patients. Wenckebach nodal anterograde atrioventricular point and basic cycle were not altered by pyridostigmine. Sinus recovery time (ms) was shorter during a 500-ms cycle stimulation (pre: 326 ± 45 vs post: 235 ± 47; P = 0.003) but not during 400-ms (pre: 275 ± 28 vs post: 248 ± 32; P = 0.490) or 600-ms (pre: 252 ± 42 vs post: 179 ± 26; P = 0.080) cycle stimulation. Pyridostigmine increased the ventricular refractory period (ms) during the 400-ms cycle stimulation (pre: 238 ± 7 vs post: 245 ± 9; P = 0.028) but not during the 500-ms (pre: 248 ± 7 vs post: 253 ± 9; P = 0.150) or 600-ms (pre: 254 ± 8 vs post: 259 ± 8; P = 0.255) cycle stimulation. We conclude that pyridostigmine did not produce conduction disturbances and, indeed, increased the ventricular refractory period at higher heart rates. While the effect explains previous results showing the anti-arrhythmic action of pyridostigmine, the clinical impact on long-term outcomes requires further investigation.